Effect of date of harvest on the yield and nutritional quality of native grass hay - Baker, J.C.; Tonn, S.R.; Paisley, S.I.; Kehler, David E.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Native grass hay meadows in three Kansas Flint Hills counties were sampled at 2-week intervals during the 1997 and 1998 growing seasons to determine the effect of harvest date on forage quality and dry matter (DM) yield. Each sample was weighed and analyzed for crude protein (CP), acid detergent fiber (ADF), and phosphorus (PHOS). The CP and PHOS contents declined, whereas ADF and DM yield increased as harvest date progressed. Although CP, ADF and DM yield were related highly to harvest date, the association for PHOS content was only moderate. Because harvest date of native grass hay can significantly influence supplemental protein needs for beef cows, mid-July harvesting appears to be the best compromise between yield and forage quality.
Keywords: Beef; Native grass; Hay; Forage quality; Cows